The European Union policies against racism, discrimination and xenophobia and their ımplementation in member states - Sayan, Pınar (My University, 2017)
AB ve kurumlarının ırksal ayrımcılık alanında geliştirdiği politikaların, maddi etkenler kadar özellikle İkinci Dünya Savaşı sonrasında geliştirilen fikir, norm ve kuralların da etkisinde olduğu fakat AB’nin yetkilerini kullanmasının sınırlı olduğu iddia edilmektedir.

It is argued that the ideas, norms and rules developed especially after the Second World War, as well as the material factors, have influenced the EU and its institutions to develop policies in the area of racial discrimination however, the use of the competences are limited.
Keywords: Avrupa Birliliği; Avrupa Birliliği Ülkeleri; Ayrımcılık European Union; Discrimination; Institutional Racism; Irkçılık; Kurumsal Irkçılık; Racism; Siyaset ve yönetim; Uluslararası ilişkiler